Ein einfaches Verfahren zur Herstellung hochbrechender dünner Schichten auf Glas - H. Brugger (CHIMIA)
Solutions of organic titanium compounds obtained by reaction of titanium tetrachloride with alcohols, ethers, esters, ketones, and other organic substances yield hard and absorption free titanium dioxide layers on glass by centrifuging the solution onto the surface and baking the hydrolyzed precipitate at 200°C.